Erythema multiforme in a Central American tapir (Tapirus bairdii) calf, clinical case report - Hernández Wolters, Luana; Striedinger Cardona, Alejandro (Frontiers in Veterinary Science, 2023)
A 7-month-old male Central American tapir with a history of recurrent respiratory diseases and repeated prolonged administration of amoxicillin with clavulanic acid presented with lethargy, severe hyperalgesia, interscapular ulcerating vesicular lesions with serosanguineous content, as well as dorsal skin peeling, oral ulcers, and thoracic limb, abdominal, and submandibular pustules with surrounding erythema and alopecia. The histopathological analysis and clinical manifestations were compatible with erythema multiforme, which was treated with daily wound cleaning and silver sulfadiazine cream application, as well as oral prednisolone for 15 days, with 5-daily tapering dose, achieving clinical improvement and an adequate cure of the disease. Vesicular dermatitis syndrome of tapirs is a disease complex including erythema multiforme, a condition rarely diagnosed since the analysis required for a definitive diagnosis are almost never performed; therefore, it is important to carry out the necessary tests that allow differentiation of the dermatopathies included in this complex of vesicular skin diseases.